Teaching efficacy of undergraduate physical education students toward concepts in physical education - Spittle, Sharna; Spittle, Michael; Itoh, Sho; Watt, Anthony P. (Frontiers in Education, 2023)
Introduction This study explored teaching efficacy for activities in physical education and how this efficacy relates to confidence and motivation in teaching physical education. Methods Students (n = 291, M age = 20.65 years, SD = 2.72) enrolled in a physical education degree course (Bachelor of Sport Science [Physical Education] or Bachelor of Education [P-12] [Primary Physical Education]) completed two questionnaires: the Physical Education Teaching Efficacy Scale (PETES) and Confidence and Motivation to Teach Primary Physical Education Questionnaire (CMTPPE) to measure teaching efficacy, and confidence and motivation teach physical education. Results Participants reported lower teaching efficacy for applying scientific knowledge and teaching students with special needs, whereas they reported higher teaching efficacy for accommodating skill level differences and for instruction. Students were generally confident in management and planning in physical education, with 2nd and 3rd year students more confident than 1st year students. Intrinsic motivation for practice (to experience stimulating sensations of fun and excitement as motives for teaching physical education) and extrinsic motivation for performance (governed by rewards and restrictions by the teacher themselves) were the stronger forms of motivation for teaching physical education, whereas intrinsic motivation for knowledge (motivation teaching physical education for pleasure and satisfaction of learning new things) and disengagement (lack of motivation toward teaching physical education) were generally lower. Confidence and motivation were significantly related to teaching efficacy for most activities and confidence was more strongly related to teaching efficacy than motivation was. A path model of the relationships indicated that both year level and course influenced confidence, with confidence then influencing motivation and teaching efficacy for teaching activities in physical education. Discussion This study has highlighted the importance of confidence to motivation and self-efficacy for teaching activities in physical education. Practical implications include the identification of areas of lower teaching efficacy in teaching physical education and the relationships between confidence, motivation and self-efficacy in teaching activities in physical education.